(untitled) (Journal of Partial Differential Equations, 2002)
" In this paper, we use the Wigner measure approach to study the semiclassical limit of nonlinear Schr00f6dinger equation in small time. We prove that: the limits of the quantum density: 03c1^2208 =: |03c8^2208|00b2 and the quantum momentum: J^2208 =: 2208Im( overline03c8^2208220703c8^2208) satisfy the compressible Euler equations before the formation of singularities in the limit system."